Implication of Religious Character Program in Improving Self-Control at State Vocational High School 1 Pedan - Hidayat, Atmaji Niti; Inayati, Nurul Latifatul (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
The ability of strong self-control can fortify faith for young people in the current era, starting from the concerns of Islamic religious education teachers at State Vocational High School 1 Pedan, sparking the implications of religious character programs aimed at increasing the faith of students to be strong, broad-minded, and have full awareness of understanding right and wrong actions. This study aims to describe the various activities carried out in the implications of religious character programs as a way to improve the religious character of students at State Vocational High School 1 Pedan. This research uses qualitative methods (field research). This research was conducted with data collection techniques through interviews, observations, and documents. Activities are carried out both daily, monthly and annually. Daily activities begin with praying both before and after learning, reading the Qur'an and short surahs, literacy, duha prayers, zuhur prayers, and school spiritists at school, if at home filled with TPA activities, tadarus, and daily amaliyah checks, which are monitored directly by their respective parents. The weekly activity called qolbu management begins with reading the Qur'an together and is filled with religious wisdom stories by the father and mother of Islamic religious education teachers and invited teachers from outside which are carried out on Friday of the first week of each month. Annual activities such as flash pesantren, Isra' Mi'raj commemoration, and the celebration of the Islamic holiday of Eid al-Fitr celebration which is filled with a gathering event between school residents.